The Practice of Political Dynasty and Kinship in Local Government of Hulu Sungai Utara District - Malta Ra Anisa Agustin; Lia Handayani; Novia Ulfah Haika; Julia Putri Herdati; Muzahid Akbar Hayat (International Journal of Law, Environment, and Natural Resources, 2022)
The practice of political dynasty has been detected in many local elections in Indonesia. This political condition may have a connection with the failure of democratization implemented in Indonesia during the Reformation era. To delve into this issue, the researchers conducted descriptive qualitative research regarding political dynasty and kinship in one of the districts in Indonesia, Hulu Sungai Utara. The researchers used Gramsci’s framework of hegemony to investigate the way political dynasty and kinship is constructed and perpetuated in Hulu Sungai Utara district. The researchers also utilized several media including print and digital media as the secondary data of this study. In the analysis of the data, the researchers discovered two ways of incumbent to perpetuate and monopolize local electoral system. Here, Abdul Wahid HK and Almien Ashar Safari (The regent and the Chief of the Provincial Legislatives Council of Hulu Sungai Utara) appear to have operated two types of power, that is soft and hard power to perpetuate their political dynasty in Hulu Sungai Utara.